CONNECTING DURING COVID: MEETING SOCIAL AND EMOTIONAL NEEDS OF VULNERABLE ELEMENTARY STUDENTS DURING A PANDEMIC - Tyler, Jamie (East Carolina University, 2022)
The COVID-19 pandemic necessitated school buildings to close in March of 2020 across the United States. From that time forward, many students remained in virtual learning environments, unable to step onto campus. The remote environments were isolating and struggled to support the academic or social and emotional needs of many students. The inability to access the supports from the physical school environment caused additional challenges for certain student populations, especially those who are considered at-risk academically or described as vulnerable due to conditions within the home environment. This mixed methods action research study, framed around the theoretical foundations of Maslow's Hierarchy of Needs and the Science of Learning and Development model, measured the impact of a social and emotional learning, online mentoring framework on levels of student engagement and connectedness. Teachers met virtually with small groups of students for six weeks, implementing lessons that focused on CASEL's social and emotional learning competencies. Both qualitative and quantitative data from surveys and focus groups measured the impact of these lessons. While the implementation of the framework did not significantly impact levels of engagement, it did yield a substantial impact on connectedness within the elementary environment. The study also explored how professional development can support staff in meeting specific needs of vulnerable students. The findings indicated that comprehensive professional development was needed to meet the needs of this population of students. Such professional development should focus on student need and support fostering relationships within the school environment in order to mitigate the educational inequities that result from isolated, remote learning environments.
Keywords: social and emotional learning pandemic; School children--Mental health--United States; COVID-19 Pandemic, 2020- --Social aspects --United States; COVID-19 Pandemic, 2020- --United States--Influence